Fabrication of cost effective and efficient dye sensitized solar cells with WO3-TiO2 nanocomposites as photoanode and MWCNT as Pt-free counter electrode. Issue 1 (January 2019) - Younas, M.; Gondal, M.A.; Dastageer, M.A.; Baig, U.
Abstract: Tungsten oxide/titanium oxide nanocomposites ( n WO3 -TiO2 ) with three different WO3 -TiO2 mass ratios ( n  = 1%, 3% and 5%) were synthesized and used as a photo-anode to fabricate dye sensitized solar cells (DSSC), in conjunction with multiwall carbon nanotube (MWCNTs) as a platinum free (Pt-free) counter electrode. It was observed that [1%WO3 -TiO2 /N719/MWCNT] DSSC exhibited an efficiency enhancement of about 40% as compared to the conventional TiO2 /dye/Pt solar cell, and 18% efficiency enhancement compared to [1%WO3 -TiO2 /N719/Pt] solar cell. The reduced electron-hole (e, h + ) recombination in the n WO3 -TiO2 nanocomposite due to reduced surface trap states, the increased accumulation of electrons at the photo-anode mediated by the photo-excitation of the dye, the efficient electron transportation and increased light absorption can be attributed to the superior performance of [ n WO3 -TiO2 /N719/MWCNT] DSSCs in general. Also n WO3 -TiO2 nanocomposite, when used as a photo-catalyst in the presence of UV radiation for the photo-catalytic degradation of Methylene blue (MB) dye, demonstrated the dye degradation efficiency as high as 99.99%. The enhanced degradation of MB dye further confirms the reduced charge (e, h + ) recombination and enhanced light absorption, the features essential for a good DSSC. In addition to the photovoltaic and photo-catalytic studies, the morphological and optical characterization of n WO3 -TiO2 nanocomposite photo-anodes films, the catalytic, electrochemical and electrical characterization of counter electrode and the fabricated DSSCs were carried out.